Wild-Type MIC Distribution for Re-evaluating the Critical Concentration of Anti-TB Drugs and Pharmacodynamics Among Tuberculosis Patients From South India - Dusthackeer, Azger; Saadhali, Shainaba A.; Thangam, Manonanthini; Hassan, Sameer; Balasubramanian, Mahizhaveni; Balasubramanian, Angayarkani; Ramachandran, Geetha; Kumar, A. K. Hemanth; Thiruvenkadam, Kannan; Shanmugam, Govindarajan; Nirmal, Christy Rosaline; Rajadas, Sam Ebenezer; et al. (Frontiers in Microbiology, 2020)
World Health Organization recommended critical concentrations (CCs) of important anti-TB drugs are universally followed for drug susceptibility testing (DST). Population and geographic based changes are expected to influence the CC of drugs among the mycobacterial species prevalent in each area. While determining the MICs for the wild-type isolates from tuberculosis patients from South India using solid (n=276) and liquid media (MGIT960: n=96; Sensititre MYCOTBI: n=50), changes in the CC were noted for isoniazid (INH) which was found to be 0.25 mg/L as against 0.1 mg/L when tested using MGIT960 and also they were dissimilar for moxifloxacin (MXF), rifampicin (RMP), ethambutol (ETH) and p-aminosalicilic acid (PAS) in liquid media using Sensititre MYCOTBI as against the WHO recommended. This could potentially lead to over diagnosis of resistance which may result in inappropriate therapeutic decision. The genomes of 16 mycobacterial isolates from this study (including two wild-types and 14 resistant strains) were subjected to whole genome sequencing to identify mutations that can be associated to drug resistance. Two of them were Beijing and rest was EAI strain types. A total of 74 mutations were identified that are known to be associated with anti-TB drug resistance in these strains. Among these five of the mutations appeared to be novel and require further analysis to confer its role in resistance. Using the serum levels determined among the South Indian population in an earlier study, pharmacodynamics (PD) were determined using the CCs for INH and RMP from current study. PD of RMP was sub therapeutic which is lesser than 10 for Cmax/MIC ratio (5.0) and lesser than 100 for AUC/MIC ratio (27.9), whereas for INH it was well above 10 (45.2) and 100 (164.4) respectively. For 8 of the patients the pharmacokinetic levels as well as the MICs of the corresponding infected strains were available. While determining the PD among these patients, RMP levels were found to be sub-therapeutic in 5 of the 8 patients. Clearly, this observation emphasis the need for optimizing the drug dosage based on PD from large scale studies in different geographical settings.